The influence of resveratrol and β-Hydroxy-β-methyl butyric acid supplementation alone or in combination on the development and health of the duodenum in Tibetan sheep - Zhang, Yu; Ji, Qiurong; Gui, Linsheng; Gebeyew, Kefyalew; Hou, Shengzhen; Wang, Zhiyou; Han, Lijuan; Yang, Chao (Frontiers in Microbiology, 2025)
Resveratrol (RES) and β-Hydroxy-β-methyl butyric acid (HMB) have been shown to exert antioxidant, anti-inflammatory effect as well as influence intestinal microbiota composition in monogastric animal. However, the mechanism by which RES and HMB regulate duodenal function in ruminants remains unclear. In this study, the effects of RES and HMB on the development and health of the duodenum in Tibetan sheep were investigated. A total of 120 early weaned Tibetan rams with similar initial body weight (15.5 ± 0.14 kg) were selected and randomly allocated into 4 groups. Each group received a basal diet supplemented with 1.5 g RES/d (RES group), 1.25 g HMB/d (HMB group), 1.5 g RES/d plus 1.25 g HMB/d (RES_HMB group), and without any additives (CON group). The results showed that RES and HMB supplementation significantly increased (p < 0.05) the villus height and the ratio of villus height to crypt depth in the duodenum. Meanwhile, the concentrations of cellulase and trypsin were increased (p < 0.05) when RES and HMB were supplemented in the basal diet. The RES group exhibited higher (p < 0.05) levels of anti-inflammatory markers (IgG, IL-6, and IL-1β), while combined supplementation of RES and HMB promoted (p < 0.05) the duodenal antioxidant capacity, as indicated by increased levels of GSH-Px and T-AOC. Furthermore, the RES group was characterized by a higher relative abundance of Butyrivibrio, while the HMB group was characterized by a higher relative abundance of Aeromonas, Rummeliibacillus, UCG-002, Ralstonia and Stenotrophomonas (p < 0.05 and LDA > 3.5). Metabolomics analysis showed that differential metabolites were significantly enriched (p < 0.05) in the cyanoamino acid metabolism, biosynthesis of secondary metabolites, protein digestion and absorption and ABC transporters. These results indicated that RES and HMB can be used as feed additives to maintain intestinal health by enhancing duodenal development, promoting digestive enzyme secretion, and improving antioxidant and anti-inflammatory capacity in Tibetan sheep.